Gosha-jinki-gan (a Herbal Complex) Corrects Abnormal Insulin Signaling. Issue 3 (2004) - Qin, Bolin; Nagasaki, Masaru; Ren, Ming; Bajotto, Gustavo; Oshida, Yoshiharu; Sato, Yuzo
Abstract : Previous studies have shown that the traditional herbal complex Gosha-jinki-gan (GJG) improves diabetic neuropathy and insulin resistance. The present study was undertaken to elucidate the molecular mechanisms related with the long-term effects of GJG administration on insulin action in vivo and the early steps of insulin signaling in skeletal muscle in streptozotocin (STZ) diabetes. Rats were randomized into five subgroups: (1) saline treated control, (2) GJG treated control, (3) 2-unit insulin + saline treated diabetic, (4) saline + GJG treated diabetic and (5) 2-unit insulin + GJG treated diabetic groups. After seven days of treatment, euglycemic clamp experiment at an insulin infusion rate of 6 mU/kg/min was performed in overnight fasted rats. Despite the 2-unit insulin treatment, the metabolic clearance rates of glucose (MCR, ml/kg/min) in diabetic rats were significantly lower compared with the controls (11.4 ± 1.0 vs 44.1 ± 1.5; P < 0.001), and were significantly improved by insulin combined with GJG or GJG alone (26 ± 3.2 and 24.6 ± 2.2, P < 0.01, respectively). The increased insulin receptor (IR)-β protein content in skeletal muscle of diabetic rats was not affected by insulin combined with GJG administration. However, the decreased insulin receptor substrate-1 (IRS-1) protein content was significantly improved by treatment with GJG. Additionally, the increased tyrosine phosphorylation levels of IR-β and IRS-1 were significantly inhibited in insulin combined with GJG treated diabetes. The present results suggest that the improvement of the impaired insulin sensitivity in STZ-diabetic rats by administration of GJG may be due, at least in part, to correction in the abnormal early steps of insulin signaling in skeletal muscle.